Speech synthesis at the Institute of Phonetics - Holtse, Peter (Annual Report of the Institute of Phonetics University of Copenhagen, 1982)
This paper gives a brief description of the more important research involving speech synthesis at the Institute of Phonetics since the Institute was founded in 1966. Further, it provides a status report for ongoing research in the shape of a more detailed account of our current activities and future plans.